STRATEGI MANAJEMEN RISIKO OPERASIONAL DALAM BISNIS E-COMMERCE UNTUK MENGHADAPI TANTANGAN DAN MENEMUKAN SOLUSI - Sulpawati; Choirunnisa, Nabila; Rohman, Hilma Fanniar (Universitas Haji Sumatera Utara, 2025)
The rapid development of e-commerce in the digital era presents both opportunities and operational challenges, such as technological disruptions, logistical risks, regulatory uncertainty, cybersecurity threats, and changes in consumer behavior. This study aims to formulate an effective operational risk management strategy by providing solutions using a qualitative approach through literature studies. The findings indicate that implementing comprehensive and adaptive risk management strategies is essential for ensuring the continuity of e-commerce businesses. The analyzed strategies—based on ISO 31000, the Value Chain approach, and the Theory of Constraints (TOC)—have proven effective in improving efficiency, data security, and customer trust. Cross-sector collaboration and clear regulatory frameworks are necessary to support the sustainability of e-commerce in Indonesia.